Currículos e a questão racial nas práticas escolares - Vanessa Regina Eleuterio Miranda de Oliveira (2002)
The focus of this investigation is the analysis of the treatment released to the racial relationships inside the scholars practices, once the thematic of the diversity and of the cultural plurality it has been discussed, with several approaches in proposed of pedagogic renewal. The research consisted of a case study, accomplished a school of the Municipal Net of Teaching of Belo Horizonte close to, presented as an institution that gives emphasis to the ethnic and racial subjects. The practices were analyzed more specifically adopted in the teaching institution that it seeks to overcome of racial prejudices, those that involve black and mestizo individuals. The collection of data included the documental research (the Project of the Plural School and the Pedagogic Political Project of the School), the observation of the daily of the school and also the accomplishment of interviews with professionals of the school. The analysis of these data went back to the identification of activities, in the curriculum of the school, which it appeared indeed for a practice inclusive, as well as for the persistence (or not) of discrimination mechanisms, veiled or explicit, in relation to the afro-Brazilian people. The study showed coincidences and divergences between the proposals in the scholar curriculum and the practical work accomplished by the school, in what he/she refers to the cultural diversity. They were also identified conflicts and consensual aspects and, still, progresses and regresses of the educational practices, related to the treatment of the racial subject.